(untitled) (Orfeu, 2022)
The book “Piano.Pears: Who plays has arrived!”, written by the teachers, pianists and songwriters Carla Reis and Liliana Botelho, was released in 2019. The material is made of 18 copyrighted works for begginers, based on teaching by imitation, so that the musical reading is considered one of the aspects to be aproached in the process of teaching a musical instrument. In this regard, the material brings us pedagogical-musical subsidies that include, for instance, keyboard topography, technique acquisition, sound exploration, creativity and understanding of musical structuring elements. The proposal brings solo and duo musicals and makes their recording available on a Youtube channel. The material consists in a practical and feasible possibility that acknowledge the real demands of piano teaching in the 21st century, offering a way that aims musical performance and creation.